Voices for change: inclusion of lived experience self-injury research, practice, education, and advocacy - Penelope Hasking; Amanda Aiyana; Sophie Haywood; Kassandra Hon; Katrina Hon; Sylvanna Mirichlis; Kirsty Stewart; Adrienne Wilmot; Stephen P. Lewis (Australian Journal of Psychology)
Objective Despite gains in research knowledge, self-injury remains unduly and widely stigmatised. This can preclude people with lived experience from playing active and important roles in the field. In this paper, we discuss how people with lived experience can offer vital contributions in this regard.Method Position paper based on narrative review.Results According to the current and especially recent literature in the field, people with lived experience of self-injury can play significant roles as researchers, educators, clinicians, and advocates.Conclusion Given the unique perspectives and strength people with lived experience of self-injury have to offer, their contributions to the field need to be harnessed and championed. This requires concerted efforts to address stigma and otherwise unhelpful discourses. In doing so, a more inclusive field with greater representation of people with lived experience can be realised. This, in turn, is conducive to advancing our understanding of self-injury and promoting the wellbeing of all people with such lived experience.